PsycEXTRA Dataset 1997
DOI: 10.1037/e495622006-016
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Drug Use: Results of Selected Empirical Investigations of Validity

Abstract: This chapter reviews the literature on factors related to quality of self-report data on drug use and discusses two series of empirical studies investigating the quality of those data. One set of analyses examined the quality of the longitudinal retrospective self-report from narcotics addicts, including validity of recent narcotics use, reliability of various measures, stability of relationships among these measures, and pattern reliability among latent constructs. Results contribute strongly to confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…Each of these indicators has been previously shown to be associated with drug use reporting (Office of Applied Studies, 2000), the validity of drug use reporting (Fendrich et al, 1999;Hser, 1997) and the CM measure (Bradburn and Sudman (1979). For purposes of these analyses, age and education were collapsed into ordinal measures.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these indicators has been previously shown to be associated with drug use reporting (Office of Applied Studies, 2000), the validity of drug use reporting (Fendrich et al, 1999;Hser, 1997) and the CM measure (Bradburn and Sudman (1979). For purposes of these analyses, age and education were collapsed into ordinal measures.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to return for follow-up interviews every 6 months over 3 years, for a total of seven interviews, and they received $50 for each completed interview. We conducted urinalysis at each follow-up interview to help ensure the veracity of self-reported drug use (Hser, 1997). However, because we did not have baseline urinalysis data, we did not use the follow-up data in the analysis.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
“…Prior research has found that the accuracy of self-reported data from drug users depends on specific subject characteristics, including types of drugs used by the sample (Hser, 1997). Studies that compared self-report data from crack users to their urinalysis results found that about half of the users who tested positive for drugs admitted to using drugs (Lu, 2001).…”
Section: Discussionmentioning
confidence: 99%